Moderasi Beragama Para Guru Madrasah Diniyah Desa Medono - Faizul Futhona Ulinnuha; Ferry Khusnul Mubarok; Qisthi Fariyani; Dwi Syafitri Mariesta Isnaini (Yayasan Al Ma'arif Dawuhan, 2025)
The development of religious understanding today is highly diverse, ranging from moderate to radical, and is easily accessible to people of all ages. In this context, religious moderation emerges as a crucial principle that encompasses a balanced, peaceful, tolerant, and compassionate approach to religious practice. Instilling these values from an early age is essential, particularly through religious education institutions such as madrasah diniyah. Teachers play a central role in the learning process, both in conveying theoretical knowledge and in shaping practical religious behavior. Therefore, their understanding of religious moderation is essential to ensure that these values are effectively transmitted to students, fostering a generation that is both religious and courteous. This study aims to analyze madrasah diniyah teachers’ comprehension of religious moderation and how they apply these values in teaching and learning activities. A descriptive qualitative research method was employed, involving all madrasah diniyah teachers in Medono Village. Data were collected through interviews and observations conducted with teachers from five local madrasas and were analyzed using established indicators of religious moderation. The findings indicate that madrasah diniyah teachers in Medono Village possess a strong understanding of religious moderation and are capable of integrating its principles into their teaching practices. This study highlights the critical role of religious education institutions in shaping moderate religious perspectives and emphasizes the importance of equipping educators with adequate knowledge and skills to promote religious moderation effectively.